Determinants of parental traditional medicine use for children during COVID-19 in Dire Dawa city administration, Eastern Ethiopia, 2023/24: Mixed community based cross-sectional study design - Mohammed Kebede; Gudeta Kusheta; Mehammedamin Jemal; Kedir Abdurehman; Netsanet Melkamu; Yakob Tadese (PLoS ONE, 2026)
Introduction Globally, 85% of the population uses traditional medicine. Ethiopia is a country with various traditional medicinal practices. However, various studies also reported traditional medicine used in children by their parents has had adverse outcomes and hospitalized them with complications. Various studies had also reported that traditional medicine use was high during COVID-19. Despite the fact that, children are particularly vulnerable population, limited studies exists regarding the prevalence, types, and determinants of parental TM use during COVID-19. In addition the existing studies were also confined to quantitative methods. Therefore, this study uses a mixed study design to explore indigenous methods of traditional medicine knowledge acquisition, preservation, preparation, storage, and dosage of herbs; barriers of disclosure; and prevalence of concomitant use. Methods A community-based concurrent mixed study design was conducted among 941 randomly selected parents from Dec 01/2023 to March 01/2024. The data was cleaned, coded, and entered in Epi-Data version 4.6 and transferred to Stata version 14.1 for analysis. Finally, an AOR with a 95% CI was computed, and variables with a p-value < 0.05 in the multivariable analysis were taken as significant factors. The qualitative data was collected from 16 selected key informants by in-depth face-to-face interviews and analyzed by using thematic analysis. Result The prevalence of parental TM use for children was 87.6%. Sibling relation to child (AOR: 0.45, 95% CI, 0.01–0.77), religion (AOR: 0.11, 95% CI, 0.04–0.29), parental TM use for themselves (AOR: 6.55, 95% CI, 1.67–25.69), easy accessibility (AOR: 2.72, 95% CI, 1.16–6.40), safety & efficacy (AOR: 4.53, 95% CI, 2.3–13.61), and TM skill in the family (AOR: 0.47, 95% CI, 0.19–0.84) were determinants of TM utilization. Lack of awareness, misperception of TM, lack of trust in HCP and negative judgment from HCP were the main-barriers for non-disclosure of TM use. Conclusion This result indicated traditional medicine use was high; nearly 9 out of 10 parents had used TM for their children during COVID-19. There was high concomitant utilization (90.6%) and high non-disclosure rate (98.1%) of traditional medicine use to health workers. Hence, it is better to give priority to strengthening the implementation of TM policy and manage accordingly.